Manuel SUÁREZ RIVERA, «La alhaja más preciosa. Historia de la biblioteca de la Real Universidad de México (1761-1815)», Ciudad de México, Universidad Nacional Autónoma de México, 2022, 777 págs. - Guibovich Pérez, Pedro M. (Cuadernos de Estudios del Siglo XVIII, 2024)
Sin resumen.